Complex rotational atherectomy in an elderly female patient with multivessel coronary artery disease. A case report - Gómez Gómez, Juan Alejandro (2023)
Rotational atherectomy is a specific procedure for managing complex coronary artery lesions, especially when there is coronary artery calcification (CAC). This technique was widely used until the last decade of the 20th century; however, although it is rarely used, it currently plays an important role in patients who could be candidates for surgical revascularization but reject surgeries due to different pathologies—such as diffuse atheromatous disease requiring long stents, in-stent restenosis, calcified ostial lesions and chronic total occlusions. Rotational atherectomy is a method that uses a diamond-coated burr to reduce the volume of atherosclerotic plaques and calcification of vessels. This device breaks up plaque into microfragments, leading to an increase in lumen diameter. These fragments, which have a tiny diameter, pass predominantly into the capillary circulation and are then absorbed by the reticuloendothelial system. Among the complications of this technique are arterial dissection, device entrapment, bradycardia and microperforation of coronary arteries. The latter can be corrected with the use of thrombin, subcutaneous fat or beads. This article reports the case of an elderly female patient with multivessel coronary artery disease associated with extensive calcification of all the coronary arteries secondary to radiotherapy received in previous years for breast cancer. The patient, not being a candidate for cardiovascular surgery, required a rotational atherectomy that resulted in a microperforation of a coronary artery but with good subsequent progress.